Students as partners in collaborative course design and educational research - Hanna-Benson, Cortney; Kroeze, Shayla; Gandhi, Radhika; Haffie, Tom; Wahl, Lindi M. (International Journal for Students as Partners, 2020)
The impact of collaborative course design is explored in this qualitative, longitudinal study of an upper-year course in which 30-40 undergraduate students co-designed the course syllabus, including both course content and assessments. In addition, the research questions and methods were co-designed by a research team involving six undergraduate student partners, an educational developer, and two faculty members. Student written work and focus-group transcripts were coded and analyzed using longitudinal interpretive phenomenological analysis. The two major themes emerging from this analysis were (a) growth (i.e., the development of academic skills, reflective practice, and personal growth that extended beyond the course), and (b) awareness (of students as a community of learners, of instructors as partners in learning, and of personal agency in learning). Personal reflections on the impact of this partnership revealed broad benefits to both students and academic staff.